ANALYSIS OF CONCEPT UNDERSTANDING IN THE PYTHAGORAS THEOREM AT STUDENTS SMPN 1 KOTABARU: ANALISIS PEMAHAMAN KONSEP TEOREMA PYTHAGORAS PADA PESERTA DIDIK SMP NEGERI 1 KOTABARU - Yuliana , Rahmi; Novianty, Evi; Yusuf, Muhammad (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
The aims of this study were 1) to analyze the conceptual understanding of students in class VIII F in understanding the Pythagorean theorem and 2) to find out the factors that cause misconceptions in class VIII F students in solving problems regarding the Pythagorean theorem. The approach used in this research is qualitative research. The method used in this research is the descriptive qualitative method. There are 3 subjects in this research. Data was collected using research instruments in the form of learning achievement tests and interviews. The results of the study stated that students' conceptual understanding subject S1 had a high conceptual understanding even though S1 was less thorough in checking answers. Whereas the S3 subject was able to explain the description of the Pythagorean theorem, it's just that the S3 could not continue the solving procedure on the Pythagorean triple problem due to lack of thoroughness, being in a hurry when working on the problem, and not understanding the Pythagorean theorem material. S2 was not able to understand some of the questions presented. It could not continue the completion procedure according to the questions due to not being thorough, easily forgetting the material that had been taught, being in a hurry when working on the questions, and not understanding the questions that had been given.